PENERAPAN METODE BERNYANYI DALAM PEMBELAJARAN MUFRADAT - Qomaruddin, Ahmad (IAIIG Cilacap, 2017)
Language is a sound symbol system used by a particular group of people to communicate and interact.Learning language Arabic is essential to understanding texts and other simple purposes,example, for spoken and written communication. The success of language learning is influenced by the learning method used,because the method is a way to facilitate a difficult thing becomes easier.One of the things that need to be learned in Arabic learning is mufradat.Mufradat is a means or media to learn Arabic,but it can not be denied that the vocabulary is very important in the learning of foreign languages including Arabic language.The application of singing method of introducing new songs and then singing the entire song, singing from stanza per stanza.With this method is expected to be able to complement references or add existing references and improve the quality of learning arabic language.